Evolution of relative sea level in Okinawa (Japan) during Holocene - Evelpidou, N.; Kawasaki, M.; Karkani, A.; Saitis, G.; Spada, G.; Economou, G. (Geografia Fisica e Dinamica Quaternaria, 2019)
Sea level indicators, such as tidal notches and beachrocks, may provide valuable information for the relative sea level (RSL) changes of an area. The study area, Okinawa, belongs to the Ryukyu Islands, Japan (Pacific Ocean), forming the emerged part of an active island arc, where the Philippine Sea plate is subducting beneath the Asian continent. Evidence of emergence has been noted by various studies. Beachrocks have also been studied, however, detailed examinations of their spatial extent and cement characteristics has not been accomplished. The purpose of this study is to discuss the RSL evolution in Okinawa through the re-evaluation of reported sea level indicators, with additional observations of beachrocks and notches and RSL predictions. Our findings suggest that the majority of Okinawa beachrocks have formed in the intertidal zone. Although the vertical uncertainty of the produced SLIPs is relatively large, there is a good agreement between the different types of sea level indicators. Comparisons with RSL predictions as well as the presence of uplifted notches further suggest that Okinawa island is generally characterized by an uplift trend, which is larger in its southern part.